PENEGAKAN HUKUM DAN MORALITAS MANUSIA DALAM PERSPEKTIF FILOSOFI - Aturkian Laia (JURNAL PANAH KEADILAN, 2023)
Law enforcement in this nation is still far from expectations, especially in terms of the moral quality possessed by law enforcers who are very messy and still maintain a corrupt mentality and this is very dangerous in realizing legal justice for all Indonesian people. Law enforcers are "primus inter pares" (first, superior, best among others). The formulation of the problem is first, how to become a complete human being. Second, how is law enforcement producing honesty, truth and justice? And research methods using normative research.